2018
DOI: 10.2169/internalmedicine.9814-17
|View full text |Cite
|
Sign up to set email alerts
|

IgA Nephropathy after Nivolumab Therapy for Postoperative Recurrence of Lung Squamous Cell Carcinoma

Abstract: Immune checkpoint inhibitors (ICIs) are becoming a common and important cancer therapy. ICIs are associated with a unique category of side effects, termed immune-related adverse events (irAEs). We herein report the case of a 72-year-old man with postoperative recurrence of lung squamous cell carcinoma who was treated with nivolumab and who developed proteinuria and a worsening kidney function. A kidney biopsy revealed IgA nephropathy. After drug withdrawal, the proteinuria improved and the deterioration of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 19 publications
2
32
1
1
Order By: Relevance
“…This led to complete [ 64 , 70 ] or partial [ 67 ] remission, the requirement of additional immunosuppressive medications such as mycophenolate mofetil (because treatment with high-dose corticosteroids had an insufficient effect and as a standard of care to treat the glomerulopathies) to obtain remission though followed by relapse [ 68 ], and no recovery in dialysis-dependent end-stage renal disease [ 69 ]. IgA nephropathy developed in two patients receiving nivolumab [ 71 , 72 ] and in one patient treated with nivolumab plus ipilimumab [ 64 ]. Drug discontinuation [ 72 ] plus steroid therapy [ 64 ] was associated with remission, whereas the other case showed a more severe AKI and in addition required renal replacement therapies for 5 months before recovery [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to complete [ 64 , 70 ] or partial [ 67 ] remission, the requirement of additional immunosuppressive medications such as mycophenolate mofetil (because treatment with high-dose corticosteroids had an insufficient effect and as a standard of care to treat the glomerulopathies) to obtain remission though followed by relapse [ 68 ], and no recovery in dialysis-dependent end-stage renal disease [ 69 ]. IgA nephropathy developed in two patients receiving nivolumab [ 71 , 72 ] and in one patient treated with nivolumab plus ipilimumab [ 64 ]. Drug discontinuation [ 72 ] plus steroid therapy [ 64 ] was associated with remission, whereas the other case showed a more severe AKI and in addition required renal replacement therapies for 5 months before recovery [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…IgA nephropathy developed in two patients receiving nivolumab [ 71 , 72 ] and in one patient treated with nivolumab plus ipilimumab [ 64 ]. Drug discontinuation [ 72 ] plus steroid therapy [ 64 ] was associated with remission, whereas the other case showed a more severe AKI and in addition required renal replacement therapies for 5 months before recovery [ 71 ]. Acute focal segmental necrotizing pauci-immune glomerulonephritis was also noted in two patients—one treated with nivolumab and one with nivolumab combined with ipilimumab [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a few reports identified IgA nephropathy as an irAE. Kishi et al reported a case of nivolumab-associated IgA nephropathy (3). The patient was a 72-year-old man who was treated with nivolumab for lung squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, compared with the standard diet, this formula food provides energy, high-quality protein and balanced nutrition, which would be expected to improve the nutritional status, as was suggested by the higher serum albumin level. Although there have been major advances in the treatment of various cancers, postoperative recurrence and metastasis remain a problem [21][22][23]. There is evidence that even after surgery, dormant tumor cells can remain in the body for a long time [24].…”
Section: Discussionmentioning
confidence: 99%